The Social Phobia of Audrey Turner in Sophie Kinsella’s Finding Audrey - Amalia Kaskita; Nungki Heriyati (STKIP PGRI Tulungagung, 2020)
This research analyses the social phobia of the character Audrey Turner in the novel Finding Audrey by Sophie Kinsella. The writer aims to reveal the main character's motivation behind her anxiety and fear in society. This happens because Audrey experiences bullying at school. Her friends intimidate and treat Audrey badly. Bullying becomes trauma for Audrey which affects her to be overly afraid when interacting with people. Audrey becomes discouraged, anti-social, low self-esteem, and high self-criticism. The social environment makes Audrey feels threatened because it is always terrorized by her traumatic event. As it is known that trauma is a mental injury that makes the nervous system threatened. So when Audrey interacts with people, warning threats come through emotional or physical reactions. Furthermore, this paper uses a qualitative method. The data are collected and represented in direct quotes from the book and analysis also supported by journals. Therefore, through this case, psychoanalysis theory by Sigmund Freud is used in order to discover the process of anxiety work and the kinds of anxiety on Audrey's psychic. Freud said that anxiety is only produced or feel from the ego but the Id, the superego, and the external world are involved in the types of anxiety. These types of anxiety are neurotic anxiety, moral anxiety, and realistic anxiety. This research reveals that Audrey's social phobia is a type of realistic anxiety that is triggered by the social world. This is due to the traumatic event which is bullying that occurs during the school.